(untitled) (Revista Educação, Artes e Inclusão, 2020)
The current armed conflicts in the world, and in particular those linked to the Islamic State System (ISIS) in Iraq, constitute a major obstacle to stable benchmarks, to a collective reading of a common culture, and to a society free from the symptoms of war. Inclusive artistic interventions are often deployed with children affected by conflict as a source of resilience and empowerment. The objective of this article is to propose entry into resilience identified during the implementation of a device of an "artistic biography" activities with coaches of an NGO and young people in a camp in Iraq. The device built was a project to "paint our caravans" as a first project with the young people in a camp. Through our experience as an artist, trainer and researcher, we observe the indicators of entry into "presence" during the artistic activities. Involvement in a collective work, self-recognition by the coaches and self-recognition in the final artistic work are the three indicators of presence that we note. Individual and collective resilience processes are complex and long and subject to many obstacles. Our article invites further investigation to build evidence to develop artistic response in humanitarian emergencies.